Kefahaman orang awam tentang arus tempur/karau/simbar/pecah (rip current) dan keselamatan pantai di Pantai Rekreasi Teluk Cempedak, Pahang - Ramli, Muhammad Zahir; Che Othman, Siti Fairuz; Yusof, Muhammad Zubir; Mohd Aliziyad, Yusairah Amani (2021)
This survey questionnaire aims to provide the Malaysian public perspective on how much beach users know and understand about rip currents, adding to international research and effort on rip current awareness, education and prevention of drowning